THE INFLUENCE OF BRAND IMAGE, PRICE, AND PRODUCT QUALITY ON THE PURCHASE DECISION OF MS GLOW ACNE SERIES IN CENTRAL CIKARANG - Erina Eka Dyah Agustin; Etty Zuliawati Zed (SEAN Institute, 2023)
In the era of globalization like today, competition in doing business is very tight. The company must be able to meet the needs of each of its consumers. To know every consumer need, companies must use the right marketing strategy. This study aims to determine the influence of Brand Image, Price, and Product Quality on the Purchase Decision of MS Glow Acne Series in Central Cikarang. The type of research used is quantitative. Sampling using Non Probability Sampling technique with purposive sampling method. The population in this study is all users of Acne Series MS Glow in Central Cikarang. The sample was determined with 80 respondents using the Slovin formula. The data collection methods used include the distribution of questionnaires and literature studies. Analysis methods are validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, hypothesis tests using determination coefficient tests, F tests and t tests. The results of the analysis show that brand image has a positive and significant effect on purchasing decisions, price has a positive and significant effect on purchasing decisions, product quality has a positive and significant effect on purchasing decisions, and brand image, price and product quality have a positive and significant effect simultaneously on purchasing decisions. The amount of influence given by the independent variable on the dependent variable was 50.4% and the remaining 49.6% was influenced by other variables outside this study.